Pelatihan Investasi Syariah Melalui Sekolah Pasar Modal (SPM) Bagi Generasi Milenial - Yuliasnita Verlandes; Nurdiana Fitri Isnaini; Agoes H. P; Ronny. M. Abar (Lembaga Pengembangan Kinerja Dosen, 2024)
Indonesia is a country with the largest Muslim population, but investment in Islamic stocks does not grow as big as convetional stocks. This arises because public investment literacy towards Islamic investment is still low. Therefore, this service activity is carried out with the aim of increasing Islamic investment literacy, especially in the millennial generation. Implementation of activities is carried out by creating a special class of Islamic capital market with the basics of Islmic stocl investments and tips and tricks for investing in the capital market with limited founds. Community service activities are carried out with partner target students and administrators of the BEM Universitas Islam Majapahit. Activities carried out from March to June 2024. The result of community service av=ctivities are in the form of increasing partner literacy regarding invetments, especially sharia stock investment and being able to create accounts through PT Phintraco Securities as a service partner.